EDUKASI PENGGUNAAN INTERNET BAGI ORANG TUA PESERTA DIDIK DI TK MUTIARA BUNDA KABUPATEN TASIKMALAYA - Jalaludin, Jalaludin; Mekwih, Mekwih; Nugraha, Aditya; Maulana, Restu Fuji Akbar; Pratama, Akmal Putra; Nurazizah, Asyfa Siti; Syarifah, Salsa Sabila; Julia, Nisa; Yuliya, Denisa; Putri, Varisa Disvarika; Hamdan, Ahmad (Jurnal Pengabdian Masyarakat Indonesia, 2024)
Parents have a very important role in accompanying their children, especially in the digital world such as the internet. Children, especially in the digital world such as the internet. For this reason, parents need to understand how to use the internet properly and wisely. The purpose of this counseling is to provide education about the use of the internet for parents of the internet for parents of students at Mutiara Bunda Kindergarten so that they can be better assist their children. The implementation method is carried out with three stages. Starting from the preparation stage, implementation, to the evaluation stage. Based on observations, it was found that students at Mutiara Bunda Kindergarten were able to operate gadgets to operate gadgets to just play online games and even surf the internet. even though. The material presented covers various aspects, such as the role of parents in accompanying children in the internet world, the benefits and risks that children may face when exploring the internet, as well as tips on supervising children in using the internet.